Validitas E-Comic Matematika Berbasis Pemecahan Masalah pada Materi Kesebangunan - Aldio Rahmata; Laila Tuljannah; Siti Chusnul Chotimah; Shofan Fiangga (JRPM (Jurnal Review Pembelajaran Matematika), 2020)
The purpose of this research is to obtain the validity of E-Comic based problem-solving in similarity material. This research is included in the development research with a quantitative approach using the ADDIE development paradigm, but just for three-stage: Analyze, Design, and Development. The instruments of data collection used the questionnaire validation and interview by experts. Based on the results of the validity test to media experts and material experts, it was concluded that the validity of mathematical e-comic based on problem-solving with similarity material reached a very valid with the average is 4,48 from a scale 1-5, so this e-comic media could be continued at the next ADDIE stage to fulfill practicality and effectiveness.